Environmental and Economic Benefits Evaluation for the CCHP System of a Thermal Power Plant in Shanghai - Yuan Yongli; Zhou Xiang; Zhao Haoliang; Shan Meiqun; Zhang Xu (Zhileng xuebao)
The energy consumption pattern and operation strategy of a combined cooling, heating and power generation (CCHP) system at a thermal power plant in Shanghai was introduced and the heat-to-electric ratio in all seasons were analyzed. The operation of the plant was optimized by evaluating the environmental and economic benefits by comparing CCHP to the system that separates cooling, heating and power generation. The results shown that, to generate the same amount of steam, the coal consumption could be reduced by 3.94 % by using the CCHP system compared to the independent system. The NOx and SO2 emissions could also be reduced by 0.1 t and 7.1 t, respectively. Furthermore, theoretically speaking, the coal consumption could be reduced by 23% and 11% in summer and transition season, respectively, after optimizing the operation of the plant.